Association Between Atopic Keratoconjunctivitis and the Risk of Recurrent Corneal Erosion - Jan, Ren-Long; Weng, Shih-Feng; Wang, Jhi-Joung; Tseng, Sung-Huei; Chang, Yuh-Shin (Frontiers in Medicine, 2021)
Purpose: To investigate the risk of recurrent corneal erosion (RCE) in patients with atopic keratoconjunctivitis (AKC). Methods: This national, retrospective, matched cohort study enrolled 184,166 newly-diagnosed AKC patients, selected from the Taiwan National Health Insurance Research Database and identified by the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) code 372.05. The control group comprised 184,166 non-AKC patients matched by age, sex, and potential comorbidities and they were selected from the Taiwan Longitudinal Health Insurance Database, 2000. Information from patients was gathered from 1 January 2004 to 31 December 2011, and both groups were traced from the index date until December 2013. The incidence and risk of RCE (ICD-9-CM code 361.42) was compared between the groups. The adjusted hazard ratio (HR) for RCE was obtained by a Cox proportional hazard regression analysis. The Kaplan–Meier analysis was performed to calculate the cumulative incidence of RCE. Results: In total, 564 AKC patients and 406 non-AKC controls developed RCE during the follow-up span. The incidence of RCE was 1.45 times higher in AKC patients than in controls (95% confidence interval [CI] = 1.27–1.64; P < 0.0001). After adjusting for potential confounders, including diabetes mellitus, keratoconjunctivitis sicca, corneal transplantation, ocular blunt trauma, corneal dystrophy, and band keratopathy, AKC patients were 1.36 times more likely to develop RCE than controls (adjusted HR, 1.36; 95% CI = 1.19–1.54; p < 0.05). Conclusions: AKC Patients had an increased risk of developing RCE and should be informed of this risk.